Quality of Life of Health Professionals During the COVID-19 Pandemic - Amanda Muglia Wechsler; Ana Cristina Zordan Rani-Yonamine (Psicologia: Teoria e Pesquisa)
Abstract The work demands and restrictions imposed by the COVID-19 pandemic can produce several impacts on health professionals. This study aimed to assess the mental suffering and quality of life of 315 professionals working in primary health care. Participants completed a sociodemographic questionnaire, the World Health Organization Quality of Life-Bref, and the Self-Reporting Questionnaire. The results showed that the professionals had a reasonable quality of life, but high rates of mental suffering. Some risk factors related to demographic, job, and lifestyle variables were observed. Conclusions highlight the importance of designing and applying specific psychological interventions for this population, which seems to be at risk of developing more severe mental conditions.